Protocolo de diagnóstico para o planejamento de alocação de equipamentos escolares: uma aplicação experimental em Caldas Novas – GO - Cruz, Leidiane Aparecida da (2024)
Considering the importance of the location of pre-school Education Units for accessibility and quality of urban life, as well as the challenges faced by the city of Caldas Novas/GO due to rapid demographic growth and history of underinvestment in education, this research aimed to develop a diagnostic protocol to assist the work of municipal technical employees in the allocation of new preschool UEs, considering the specific urban and demographic context of Caldas Novas/GO. To this end, a practical and quantitative methodology was applied, characterized by bibliographic and experimental analysis, resulting in the creation of a protocol based on Geographic Information Systems - GIS. The research was divided into three main phases. In the first, the essential concepts about school equipment and its relationships with the city were established, focusing on accessibility and quality of urban life. The second phase focused on developing a protocol through a comprehensive analysis of 47 academic documents, categorizing and systematizing the methodological procedures. The result was the creation of a diagnostic protocol for planning the allocation of school equipment in urban areas. The developed protocol consists of five main scripts. The Capacity roadmap aims to identify imbalances in the supply capacity. The Coverage roadmap analyzes the spatial distribution of the offer in the urban context, identifying areas that benefit or not. The Accessibility roadmap evaluates the shift between demand and supply. The Occupation of urban space and Social vulnerability routes seek to assess the spatial distribution of demand and identify socioeconomically unfavorable areas, respectively. The research validated the protocol experimentally in Caldas Novas, identifying priority areas for the allocation of new preschool Education Units. It was proposed to locate 13 new standard Type 2 Proinfância units, demonstrating the feasibility and effectiveness of the protocol in guiding municipal management for decision-making. It concludes on the continued importance of developing and disseminating methodologies for allocating teaching units to promote accessibility and quality of urban life.